Pengaruh Tingkat Kecerdasan Emosional Terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas V - Friska Anggun Cintami; Fajar Cahyadi; Muhammad Arief Budiman (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to determine the score of emotional intelligence, the score of mathematical problem solving abilities and whether or not there was an influence between the level of emotional intelligence on students' mathematical problem solving abilities. This research is a quantitative research with ex-post facto research design. The data collection method in this study was a questionnaire to measure the level of emotional intelligence and a test to measure students' mathematical problem solving abilities. Based on the results of the data processing, the values of the T-Test and F-Test (ANOVA) were obtained. T-Test results obtained sig value of 0.000 and t-count value of 6.696. The value of sig<0.05 or 0.000<0.05. The value of t arithmetic > t table or 6.696> 1.6973. The results of the F-Test (ANOVA) obtained a sig value of 0.000 and a calculated f value of 44,842. The value of sig < 0.05 or 0.000<0.05. The value of f table is 1.84. The value of f arithmetic > f table or 44,842>1.84. Then there is a significant influence between the level of emotional intelligence on the ability to solve mathematical problems